Correlations between Physical Activity, Work Duration, and Stress on the Risk of Musculoskeletal Disorders in Online Motorcycle Drivers in Surakarta - Isna Andriani; Sumardiyono; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Motorcycle taxi drivers drive motorcycles with a static posture and there are significant deviations in angles of certain body joints that trigger susceptibility to movement system injuries, namely musculoskeletal disorders (MSDs). The study aimed to analyze the correlation between the determinants of MSDs, namely physical activity, work duration, and stress on the risk of MSDs incidents in online motorcycle taxi drivers in Surakarta.Subjects and Method: This observational analytical study with a cross-sectional study approach. A sample of 250 online motorcycle taxi drivers in Surakarta was selected using a cluster random sampling technique. The dependent variable of the study was MSDs. The independent variables of the study were physical activity, duration of work, and stress. The data collection technique was conducted through interviews by using questionnaire sheets with instruments i.e. International Physical Activity Questionnaire (IPAQ), Work Stress Scale (WSS), and Nordic Body Map (NBP). Data analysis was carried out using a multivariate STATA application with multiple binary logistic regression.Results: The risk of MSDs in online motorcycle taxi drivers in Surakarta increased with the age of older than or equal to 34 years (OR= 2.66; CI 95%= 1.54 to 4.59; p= <0.001), BMI of more than 25 (OR= 1.33; CI 95%= 0.77 to 2.27; p= 0.303), work duration of more than 4 hours per day (OR= 2.43; CI 95%= 1.24 to 4.78; p= 0.010), high stress level (OR= 1.58; CI 95%= 0.89 to 2.83; p = 0.126), and status as an active smoker (OR= 1.27; CI 95%= 0.74 to 2.19; p= 0.378). The risk of MSDs in online motorcycle taxi drivers in Surakarta decreased with active physical activity (OR= 0.36; CI 95%= 0.15 to 0.86; p = 0.021). Age, BMI, physical activity, work duration, stress, and smoking status influenced the risk of MSDs by 8.2%, and the rest were influenced by other determinants.Conclusion: There is a statistically significant correlation between age, physical activity, and duration of work on the risk of MSDs, however, there was no significant correlation between BMI, stress, and smoking status on the risk of MSDs. Keywords: Physical activity, stress, musculoskeletal disorders, motorcycle taxi drivers